Dihydroflavonols from the leaves of Macaranga recurvata and their cytotoxic and antioxidant activities. - Mulyadi, Tanjung (Journal of Chemical And Pharmaceutical Reseach 3/668 Ma;viya Nagar, Jalpur Rajasthan India-3020I7, 2014)
Three dihydroflavonol derivatives, macarecurvatin A (1), macarecurvatin B (2), and 6,8-diisoprenylaromadendrin (3) have been isolated from the leaves of Macaranga recurvata. The structures of these compounds were determined based on UV, IR, HRESIMS, 1D and 2D NMR data. All of compound isolated were evaluated for their inhibitory effect on scavenging DPPH radical and their growth inhibition on MCF7, and tamoxifen-resistant MCF7(MCF7/TAMR) breast cancer cell showed high antioxidant and high cytotoxic activities.